Influence of Human Resource Quality and Management Commitment on the Quality of Accounting Information - Octavia, Evi; R. Ait Novatiani; Rachmawati, Rima (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to analyze and test in more depth the influence of the quality of human resources and management commitment on the quality of accounting information. This research needs to be carried out because several cases related to financial reports have caused accounting information to be of poor quality. Multiple linear regression is used in this study's data analysis for both descriptive and verifying purposes carried out at PT PLN Distribution West Java with 30 respondents. A significant association is indicated by the multiple correlation coefficient value of 0.785. These findings suggest a robust and favourable correlation between the quality of accounting information and management commitment and human resources. This implies that if management is dedicated and human resources are qualified, the quality of accounting information will be higher. The quality of human resources and management commitment have a 61.6% influence on the quality of accounting information, according to the coefficient of determination value of 0.616. The results of the descriptive analysis that has been carried out are in the sufficient category, meaning that there are still several things that are not optimal in the Human Resource Quality indicators, especially the results of the training that is carried out is not optimal. Descriptive analysis of Management Commitment is not optimal, namely there is still a lack of awareness of maintaining commitment as something that should be. The results of the descriptive analysis on the Quality of Accounting Information are in the sufficient category, meaning that there are still things that are not optimal, especially there are still obstacles when operating the system and the system still does not make it easy to find the information needed.